ANALISIS DISKRIMINAN UNTUK MENENTUKAN INDIKATOR GARIS KEMISKINAN - Dadang Sukandar; Nani Sufiani Suhanda; Leily Amalia; Khairunisa Khairunisa (Jurnal Gizi dan Pangan, 2008)
The objectives of this study are to: 1) determine poverty line gold standard of farmers, 2) compare the gold standard with existing poverty line i.e. Sajogyo, Central Bureau of Statistics, BKKBN, World Bank US $ 1 and World Bank US $ 2, and 3) derive poverty indicators. This research was conducted in Subang, West Java. As many as 522 farmer households were collected as sample through stratified random sampling with proportional allocation. Data collected include socio-economic, income, expenditure, food consumption, health, anthropometry, agriculture aspects and living cost component and their prices. The Gold Standard was obtained through distribution standard normal while poverty indicator was derived through discriminant analysis. The results show that the poverty line gold standard of farmer is Rp. 457,558/capita/month which is equivalent to 2.29 gram of gold/capita/month. Discriminant analysis give five indicators of poverty namely, number of households member, husband education level, nutritional status of children, frequency of egg consumption, and land size manage by farmers.